2022
DOI: 10.3389/fcell.2021.789948
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cell Death: Pyroptosis, Ferroptosis, Apoptosis and Necroptosis in Osteoarthritis

Abstract: New research has shown that the development of osteoarthritis (OA) is regulated by different mechanisms of cell death and types of cytokines. Therefore, elucidating the mechanism of action among various cytokines, cell death processes and OA is important towards better understanding the pathogenesis and progression of the disease. This paper reviews the pathogenesis of OA in relation to different types of cytokine-triggered cell death. We describe the cell morphological features and molecular mechanisms of pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 207 publications
(207 reference statements)
0
109
0
Order By: Relevance
“…Recent studies on aging-related diseases have indicated that ferroptosis contributes in the pathogenesis of Alzheimer's disease (230-232), Parkinson's disease (233,234), Huntington's disease (235), Depression (236-238), Osteoarthritis (239), Myocardial ischemia and reperfusion (MI/R) (240)(241)(242), Atherosclerosis (243, 244), and Diabetes (245,246). Notably, quercetin shows iron-chelating activity and effectively decrease iron deposition in the hearts, kidneys and liver of iron-dextran-overloaded mice (247), and protects bone marrow-derived mesenchymal stem cells from erastin-induced ferroptosis through antioxidant pathway (248).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Recent studies on aging-related diseases have indicated that ferroptosis contributes in the pathogenesis of Alzheimer's disease (230-232), Parkinson's disease (233,234), Huntington's disease (235), Depression (236-238), Osteoarthritis (239), Myocardial ischemia and reperfusion (MI/R) (240)(241)(242), Atherosclerosis (243, 244), and Diabetes (245,246). Notably, quercetin shows iron-chelating activity and effectively decrease iron deposition in the hearts, kidneys and liver of iron-dextran-overloaded mice (247), and protects bone marrow-derived mesenchymal stem cells from erastin-induced ferroptosis through antioxidant pathway (248).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…As an independent form of cell death, ferroptosis can be clearly distinguished from other forms of cell death by the accumulation of lethal reactive oxygen species (ROS) and lipid peroxidation products caused by iron-dependent reactions ( Table 1 ; Dixon et al, 2012 ; Wu et al, 2012 ; Liu and Levine, 2015 ; Chen et al, 2016 ; Xie et al, 2016 ; Galluzzi et al, 2017 ; D’Arcy, 2019 ; Xu et al, 2019 ; Demarco et al, 2020 ; Mizushima and Levine, 2020 ; Nah et al, 2020 ; Khan et al, 2021 ; Li et al, 2021 ; Nadeem et al, 2021 ; Yang et al, 2021 ; Braicu et al, 2022 ; Lei et al, 2022 ). Ultrastructural changes in mitochondria are the most prominent morphological features of ferroptotic cells.…”
Section: The Process and Regulation Of Ferroptosismentioning
confidence: 99%
“…The regulation of chondrocyte survival is important for the maintenance of proper cartilage structure and function. Apoptosis is an active, physiological process of cell death, playing a critical role in retaining the homeostasis of tissues and cells [ 34 ]; it is regulated by various genes, such as those of the BCL-2 family, identified as controllers and inductors of this mechanism [ 35 ]. Dysregulation of apoptosis is, thus, associated with a variety of diseases including inflammatory and degenerative disorders such as OA and RA [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%